The prognostic significance of malnutrition in older adult patients with acute ischemic stroke - Jiang, Tian-Tian; Zhu, Xing-Yu; Yin, Yan-Wei; Liu, Hong-Jin; Zhang, Guang-Yun (Frontiers in Nutrition, 2025)
BackgroundMalnutrition is associated with an unfavorable prognosis; however, malnutrition in hospitalized patients is frequently overlooked by clinicians. This highlights the importance of accurately assessing nutritional status and providing appropriate nutritional supplementation. The most appropriate nutritional assessment tool for predicting the short-term prognosis of older adult patients with Acute Ischemic Stroke (AIS) was identified from five nutritional assessment tools, including the Prognostic Nutrition Index (PNI), the Hemoglobin, Albumin, Lymphocyte and Platelet (HALP) Score, the Naples Prognostic Score (NPS), the Geriatric Nutritional Risk Index (GNRI), and the Controlling Nutritional Status (CONUT) Score.MethodsA total of 585 older adult patients with Acute Ischemic Stroke (AIS) were retrospectively analyzed and divided into two groups according to the modified Rankin Scale (mRS) score. The first group, comprising 111 cases, was classified as having a poor prognosis (mRS score > 2), while the second group, consisting of 391 cases, was classified as having a good prognosis (mRS score ≤ 2). A total of five nutritional assessment tools, including PNI, HALP Score, NPS, GNRI, and CONUT, were employed to evaluate the nutritional status of older adult patients with AIS and for the analysis of the relationship between nutritional status and prognosis. The incremental value of five nutritional assessment tools in predicting patient prognosis was compared by means of the Integrated Discriminant Improvement Index (IDI) and the Net Reclassification Index (NRI). The efficacy of each nutritional assessment tool in forecasting the incidence of unfavorable outcomes in older adult patients with AIS within a one-year timeframe was evaluated by utilizing the area under the receiver operating characteristic curve (AUC), calibration curves, and decision analysis curves. Comparative analyses were also conducted.ResultAmong the five nutritional assessment tools, the PNI (AUC: 0.619, 95% CI: 0.560–0.679, p < 0.001) and HALP score (AUC: 0.612, 95% CI: 0.552–0.672, p < 0.001) demonstrated a significantly greater area under the ROC curve (AUC) compared to the NPS (AUC: 0.597, 95% CI: 0.536–0.658, p = 0.002), CONUT score (AUC: 0.582, 95% CI: 0.520–0.644, p = 0.009), and GNRI (AUC: 0.590, 95% CI: 0.529–0.651, p < 0.001). When compared to BMI, PNI exhibited a more pronounced improvement in the integrated discrimination index (IDI: 0.0203, p = 0.0061). Similarly, the net reclassification index (NRI) also showed a significant improvement (NRI: 0.2422, p = 0.024), indicating the superior performance of PNI in risk stratification.ConclusionAmong the five types of nutritional assessment tools employed in this study, the PNI was the most effective at predicting a poor prognosis at one year in older adult patients with AIS.